A Comparative Study of Intellectual and Literary Orientations of Sohrab Sepehri and Walter de la mare Based on Sigmund Freud's Theory of Defense Mechanisms - Vahid keshavarz (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Walter de la Mare and Sohrab Sepehri live in turbulent periods of contemporary histories of their countries. In these circumstances, many of their contemporaries draw on political demands and social issues as inspiration to create literary works. These two, however, follow a kind of mild Romanticism and are more concerned with emotional experiences rather than social and political developments. This tendency causes some critics to accuse them of a "lack of social commitment" and "irresponsibility" for fellow human beings, but these poets' humanitarian poems cast doubt on such claims. The main purpose of this paper is to try to probe into the reasons involved in the formation of these poets' Romantic tendencies. To do so, we have deployed Freud's "Psychological Defense Mechanisms". The compatibility of the poems with many components of this theory suggests that such divergence from the dominant intellectual trend, could be a subconscious "psychological defense mechanism" manifested in these poems.